Determination of norvancomycin epidemiological cut-off values (ECOFFs) for Staphylococcus aureus, Staphylococcus epidermidis, Staphylococcus haemolyticus and Staphylococcus hominis. (14th October 2020) - Yang, Qiwen; Li, Xue; Jia, Peiyao; Giske, Christian; Kahlmeter, Gunnar; Turnidge, John; Yu, Yunsong; Lv, Yuan; Wang, Minggui; Sun, Ziyong; Lin, Jie; Li, Yun; et al.
Abstract: Objectives: To determine the epidemiological cut-off values (ECOFFs) of norvancomycin for Staphylococcus aureus, Staphylococcus epidermidis, Staphylococcus haemolyticus and Staphylococcus hominis . Methods: We collected 1199 clinical isolates of Staphylococcus species from five laboratories located in four cities in China. MICs and inhibitory zone diameters of norvancomycin were determined by broth microdilution and the disc diffusion method, separately. ECOFFs of norvancomycin for four species were calculated by ECOFFinder software following EUCAST principles. Methicillin and vancomycin resistance genes ( mecA / mecC and vanA / vanB / vanC / vanD / vanE ) were screened for by PCR in all isolates. Pearson correlation and χ 2 test were used to calculate the correlation of MICs and inhibition zone diameters, and MICs and resistance genes, respectively. Results: MICs of norvancomycin for all strains from five laboratories fell in the range of 0.12–2 mg/L. ECOFFs of norvancomycin were determined to be 2 mg/L for S. epidermidis and S. haemolyticus and 1 mg/L for S. aureus and S. hominis . A weak correlation was observed between MIC values and zone diameters for S. haemolyticus (r = −0.36) and S. hominis (r = −0.26), while no correlation was found for S. epidermidis and S. aureus . The mecA gene was detected in 63.1% of Staphylococcus, whereas no isolate carried mecC, vanA, vanB, vanC, vanD or vanE . ECOFFs of norvancomycin were not correlated with mecA gene carriage in Staphylococcus species. Conclusions: ECOFFs of norvancomycin for four Staphylococcus species were determined, which will be helpful to differentiate WT strains. The correlation of MICs and zone diameters of norvancomycin was weak in Staphylococcus species.